Complications and Outcomes of Chimeric Free Flaps: A Systematic Review. (21st May 2019) - Ettyreddy, Abhinav R.; Chen, Collin L.; Zenga, Joseph; Simon, Laura E.; Pipkorn, Patrik
Abstract : Objective: Ablations of locally advanced or recurrent head and neck cancer commonly result in large composite orofacial defects. Chimeric flaps represent a unique surgical option for these defects, as they provide diverse tissue types from a single donor site. The purpose of the study was to consolidate the literature on chimeric flaps with regard to postoperative complication rates to help inform surgical decision making. Data Sources: The librarian created search strategies with a combination of keywords and controlled vocabulary in Ovid Medline (1946), Embase (1947), Scopus (1823), Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, and Clinicaltrails.gov (1997). Review Methods: Candidate articles were independently reviewed by 2 authors familiar with the subject material, and inclusion/exclusion criteria were uniformly applied for article selection. Articles were considered eligible if they included patients who received a single chimeric flap for reconstruction of head and neck defects and if they provided data on complication rates. Results: A total of 521 chimeric flaps were included in the study. The major complication rate was 22.6%, while the minor complication rate was 14.0%. There were 7 flap deaths noted in the series. Median operative time and harvest time were 15.0 and 2.5 hours, respectively. Conclusion: Chimeric flaps represent a viable option for reconstruction of complex head and neck defects and have complication rates similar to those of double free flaps and single free flaps with locoregional flap while only modestly increasing total operative time.